Contrôle de l’intimité et normes de genre : la qualification d’un comportement suspect et sa contestation dans le cadre de perquisitions et d’assignations à résidence pendant l’état d’urgence - Flora Hergon (Genre, Sexualité et Société)
This article analyzes the control of intimacy in the context of searches and house arrests, following the November 13, 2015 attacks in France. The article relies on the analysis of repeated interviews and files of individuals who were suspected of Islamic radicalization and who experienced a search and/or a house arrest. It analyzes the state attention paid to religious practices, intertwined with presumed unequal gendered behaviors between suspected men and women. Yet appeals can constitute a tool for contesting this suspicion of a transgression of social norms. The promotion of a gendered sociability, of the model of the good father or of a liberal masculinity highlights a reappropriation of normative categories by suspected subjects in order to prove a private life in conformity with social norms. This study on the use of gender norms to justify or to contest some security measures article extends the analysis of state control of intimacy, beyond the domestic space, to the arena of administrative justice.